Weight of the resected specimen after transurethral resection as a new predictive variable for recurrence of non‐muscle‐invasive bladder tumour. (26th October 2012) - De La Peña, Enrique; Hernández, Virginia; Blázquez, Cristina; Martin, Maria D.; Díaz, Francisco J.; Capitán, Carlos; Alemany, Isabel; Llorente, Carlos
Abstract : What's known on the subject? and What does the study add? Size is one of the currently used variables for predicting recurrence and progression of non‐muscle‐invasive bladder tumour (NMIBT), but size is subjective and not easy to measure. We evaluate a new and objective variable to replace size, not previously reported. We assess the weight of the transurethral resection specimen as a predictor of recurrence and progression and conclude that this outperforms size as a predictor of recurrence of NMIBT. OBJECTIVE: To evaluate the role of the weight of the resected specimen after transurethral resection as a predictive factor for recurrence and progression of non‐muscle‐invasive bladder tumour (NMIBT). PATIENTS AND METHODS: The weight of the resected tumour was measured consecutively in 144 subjects who underwent transurethral resection of bladder tumours at our institution. The median (interquartile range [IQR]) follow‐up was 58 (61.3) months. The probability of recurrence and progression at 1 and 5 years were calculated using the currently accepted variables. Thresholds for the specimen weight were determined according to percentiles and receiver–operating characteristic curves. RESULTS: The median (IQR) weight of the specimen was 6 (16) g. Multivariate analysis showed that the weight of the resected specimen was an independent predictive risk factor for recurrence at a threshold value of 6 g with a hazard ratio of 1.7 (95% confidence interval: 1.048–2.761) P = 0.03. Progression was not associated with the weight of the resected specimen. CONCLUSIONS: The weight of the resected specimen is a new variable for predicting the risk of recurrence of NMIBT. Tumours weighing >6 g, according to the present data, have a 1.7‐fold higher likelihood of recurrence than those tumours that weigh less.